A survey on skin cancer detection using skin temperature variation analysis - Safrin, A. Noora; Pooja, B.; Hema, K.; Padmapriya, P.; Narayanamurthy, Vigneswaran; Fahmi, Samsuri (Academic Publications, 2018)
All over the world, in recent years people were suffering from various types of cancer, the skin cancer becomes emerging in that. In India about 2 in 10 cases people are suffering from Melanoma type of skin cancer. In recent years there is no cancer screening tool available for early diagnosis of skin cancer. The existing method, skin cancer can be detected by the doctors (or) self-examination by the person (or) through certain technique which can capture only images (or) through invasive method like biopsy in the abnormal cell proliferated region. Proposed system is implementation of infrared thermal sensor in a noncontact manner which detects the temperature of the epidermal layer of skin, where the temperature of the skin varies for the subjects if they are suffering from cancer.